Identification of a novel Pfkfb1 mRNA variant in rat fetal liver - Cosin Roge, Jesús (2013)
The bifunctional enzyme 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase (PFK-2/FBPase-2) catalyzes the synthesis and degradation of fructose-2,6-bisphosphate, a key metabolite in the glucose homeostasis. Four genes, Pfkfb1-4, have been characterized in mammals that code for several isoforms generated by alternative splicing through the control of several promoters and 5' non-coding exons. Here, we characterize in fetal rat liver new mRNA variants which are transcribed from a new Pfkfb1 gene promoter. The long variant codes to a new isoform (FL-PFK-2) that would be of relevant function to modulate the transition of fetal to adult liver metabolism.